Pathophysiology of trauma-induced coagulopathy - Schöchl, Herbert; Schmitt, Felix; Maegele, Marc (Hämostaseologie, 2024)
Trauma-induced coagulopathy (TIC) is a complex hemostatic disturbance that can develop early after a major injury. There is no universally accepted definition of TIC. However, TIC primarily refers to the inability to achieve sufficient hemostasis in severely injured trauma patients, resulting in diffuse microvascular and life-threatening bleeding. Endogenous TIC is driven by the combination of hypovolemic shock and substantial tissue injury, resulting in endothelial damage, glycocalyx shedding, upregulated fibrinolysis, fibrinogen depletion, altered thrombin generation, and platelet dysfunction. Exogenous factors such as hypothermia, acidosis, hypokalemia, and dilution due to crystalloid and colloid fluid administration can further exacerbate TIC. Established TIC upon emergency room admission is a prognostic indicator and is strongly associated with poor outcomes. It has been shown that patients with TIC are prone to higher bleeding tendencies, increased requirements for allogeneic blood transfusion, higher complication rates such as multi-organ failure, and an almost fourfold increase in mortality. Thus, early recognition and individualized treatment of TIC is a cornerstone of initial trauma care. However, patients who survive the initial insult switch from hypocoagulability to hypercoagulability, also termed “late TIC,” with a high risk of developing thromboembolic complications.
Gesehen am 25.07.2024
Zusammenfassung in deutscher Sprache